HUBUNGAN KECEPATAN BOLA DENGAN INDIKATOR VARIABEL KINEMATIKA PITCHER BASEBALL DALAM KONDISI KELELAHAN - Muhamad Sigit Darmawan, - (2019)
The purpose of this study was to study the relationship of speed with variable indicators pitch pitcher baseball. The sample in this study were six baseball pitchers of the Universitas Pendidikan Indonesia who had practiced baseball pitchers. The method used in this research is quantitative descriptive. Kinematic analysis uses a Sony 32GB HDR-PJ540 camera, a Go-pro camera, to see the speed of the ball using the Radar Speed Gun. Data analysis using SPSS version 21 with hypothesis testing through bivariate correlation. The results of the analysis and calculation of the data revealed from the 19 indicators discussed, only two indicators have a significant relationship to the speed of the ball, namely the angle of the Knee flexion in the lead foot contact phase and the angle of the lateral trunk tilt in the realese ball phase. Keywords: Kinematic, Biomechanics, Pitchers, Baseball